Discrete analysis for the America west coast rainfall predictability using El Niño/Southern Oscillation relationships - Cid Serrano, Luis Ramón (2013)
poster -- Universidad de Costa Rica. Centro de Investigaciones Geofísicas, 2013. Sugerencia para referencias: - Cid, L., S. Ramírez, E. Alfaro & D. Enfield, 2013. Discrete analysis for the America west coast rainfall predictability using El Niño/Southern Oscillation relationships. Memorias del 3er Congreso de Oceanografía Física, Meteorología y Clima del Pacífico Suroriental. Sesión de Variabilidad Climática (poster VC.P3). Santiago, Chile. 16-18 de octubre de 2013.